DETERMINATION OF FACTORS RESPONSIBLE FOR THE CHANGE IN VEGETAL COVER IN KATSINA TOWN (FUDMA JOURNAL OF SCIENCES, 2020)
The study examined the factors responsible for change in vegetation cover between 1999 and 2019.  Decadal data for climatic variable (rainfall and temperature), Landsat satellite images and population data of 1999, 2009 and 2019 were used. Land use/Land cover Change Detection, linear time series and Spearman rank order correlation analysis were used. The results revealed that the extent change between (1999-2009) and (2009-2019) for built-up, vegetation and bare surface were; (+91.66, +276.41), (-4.06, -40.42) and (-27.44, -23.5) respectively. There were increasing trends in the built-up environment, population growth and rainfall at the rate of (19.3 km2 per-10), (110116 persons per-10) and (231.5mm per-10) respectively. There were decrease trend of temperature and vegetation cover at the rate of (-1.15oC per-10) and (-19.3 km2 per-10) respectively.  Negative relationship exist between population growth (r = -0.938), built up (r = -0.987), rainfall (r = -0.982) and vegetation cover, while positive relationship exist between temperature (r = 0.965) and vegetation cover. The study conclude that temperature is the major factor influencing the loss in vegetation cover, rapid population growth and urban expansion were experienced during the study period. The study recommend five (5) trees should be planted per built-up structure in order to create more carbon sink and to improve vegetal resource which were affected by human activities and  changing climatic variables
Keywords: Population Growth, Climate Change, Vegetation, Satellite Imageries